The Inverted Pyramid Model - A Physical Perspective to Understand How Risk is Undermined in Designing Complex Financial Instruments - Singh, Shveta (Indian Journal of Finance, 2009)
The recent financial upheavals that rocked the International Financial Systems across the world are evidence of how very sophisticated technical theories and tools often lose out to conventional wisdom a.k.a. common sense. What even some Wall Street stalwarts failed to look into or rather ignored are the rather mundane applications of physical science, pressure and force that act upon an object as you build upon it. It was plain and simple greed on the parts of some which has led to an international financial crisis not seen before. And this time too, it is basic conventional theories and fundamental concepts and sciences that hold the answer to what went wrong. What financial wizards chose to ignore in designing the sophisticated sounding collateral debt obligations was the risk that would then be piling up on the inherent base security acting as the bottom of an inverted pyramid that started shaping up. This paper invokes a model that’ll help in analyzing the force in terms of increased systematic and unsystematic risk that started building up not just on the underlying security but indeed on the CDOs and the financial environment surrounding these specialized derivatives.